Drone Laying Honey Bee Workers in Queen Monitoring Cages. Issue 3 (15th June 2022) - Fine, Julia D; Litsey, Eliza M
Abstract: Techniques to monitor honey bee ( Apis mellifera ) egg production in cages allow researchers to study how different environmental factors contribute to reproduction. However, although the conditions required to facilitate queen egg production in a laboratory setting have been established, limited work has addressed the requirements for stimulating and monitoring worker egg laying. Here, we documented that drone laying workers will lay eggs in Queen Monitoring Cages (QMC), specialized cages designed to facilitate queen egg laying under controlled conditions. Egg production and worker mortality were compared between QMCs containing queens and those containing drone laying workers. High-definition images of the last abdominal segments of living first-instar larvae hatched from worker laid eggs and those putatively laid by queens were qualitatively compared to identify candidate characteristics to determine their sex.